1975
DOI: 10.1021/bi00697a009
|View full text |Cite
|
Sign up to set email alerts
|

Structural and enzymic properties of adenine 1-oxide nucleotides

Abstract: We decribed the preparation of adenine 1-oxide nucleotides by oxidation of the natural compounds with monopermaleic acid in aqueous solutions at neutral pH, with an overall yield after chromatographic purification between 75 and 80%. If irradiated, the adenine 1-oxide nucleotides undergo a photochemical rearrangement reaction, the main photoproducts in aqueous solution at alkaline pH being the corresponding isoguanine nucleotides. The modified ring vibration pattern of the 1-oxide analogues as well as the 13C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

1977
1977
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 52 publications
0
17
0
2
Order By: Relevance
“…o'ITP was prepared by oxidative deammatlon of adenosine-1 -oxide 5'.triphosphate [7,8]. Other natural or modified nucleotides, enzymes and substrates were supplied by Boehringer Mannheim.…”
Section: Chemicalsmentioning
confidence: 99%
“…o'ITP was prepared by oxidative deammatlon of adenosine-1 -oxide 5'.triphosphate [7,8]. Other natural or modified nucleotides, enzymes and substrates were supplied by Boehringer Mannheim.…”
Section: Chemicalsmentioning
confidence: 99%
“…In 1975, Mantsch 41 et al reported that isoguanine nucleotides are not recognized by the mitochondrial endometrial translocation enzyme system, but they can be well recognized by mitochondrial phosphatases in the inter-membrane space. They are also involved in phosphoryl group transfer reactions.…”
Section: Mispairingmentioning
confidence: 99%
“…196 And in 1974, Holy 197 et al reported that isoG can also inhibit inducible E. coli binding site. In addition, in 1975, Mantsch 41 et al reported that its 5 0 -di-and -tri-phosphates can strongly bind and inhibit glutamic acid dehydrogenase. In 1988, Wissler 198 et al reported that isoG also acts as an essential constituent of Cu(II)-containing ribonucleic acid produced by cultured pig macrophages.…”
Section: More Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Μαζί με την 2΄-αμινογουανοσίνη,83 η ισογουανοσίνη είναι ο μόνος γνωστός φυσικός νουκλεοζίτης γουανίνης που δρα ως αντιβιοτικό. Οι διφωσφορικοί και τριφωσφορικοί εστέρες της ισογουανοσίνης είναι ισχυροί αναστολείς της αφυδρογονάσης του γλουταμινικού οξέος 84. Η σύνθεση της μπορεί να γίνει εύκολα από φωτοϊσομερίωση του 1-οξειδίου της αδενοσίνης (68) 84.…”
unclassified